SLEEP DISTURBANCES AMONG PATIENTS WITH BIPOLAR AFFECTIVE DISORDER IN THE CURRENT DEPRESSIVE EPISODE ASSESSED BY THE SLEEP-50 SCALE AT THE NATIONAL INSTITUTE OF MENTAL HEALTH, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence, patterns, and related factors of sleep disturbances using the Sleep-50 scale in patients with bipolar disorder (BD) during a current depressive episode receiving treatment at the National Institute of Mental Health.Subjects and methods: A cross-sectional descriptive study was conducted on 123 patients diagnosed with bipolar affective disorder in a current depressive episode according to ICD-10 criteria from January 2025 to October 2025.Results: Based on the Sleep-50, sleep disturbances were identified in 80.5% of patients. The most prevalent domains were insomnia (84,8%), narcolepsy/hypersomnolence (24,2%) nightmares (20,2%), restless legs/periodic limb movements (9,1%), obstructive sleep apnea (7,1%), and circadian rhythm disorder (4,0%). Among those with insomnia, difficulty initiating sleep (82,1%), difficulty maintaining sleep (66,7%), and early morning awakening (29,8%) were reported. Mean total sleep time was 5,9 ± 1,7 h/night while time in bed averaged 8,7 ± 1,5 h, with poor/very poor sleep efficiency in 75,8% of patients. Significant correlates of sleep disturbance were age ≥ 40 years (OR = 3,04; 95% CI: 1,14–8,09; p = 0,023) and ≥3 hospitalizations (OR = 12,63; 95% CI: 4,18–38,10; p
Keywords: Bipolar disorder, depressive episode, Sleep 50, insomnia, sleep disturbance